Warfare and Society in Europe, 1792- 1914. - Wawro, Geoffrey (Routledge, 1999)
Combining original research with the latest scholarship Wawro examines war and its aftermath from Napoleonic times to the outbreak of WW1. The book highlights the interplay of society, politics and military decision making in Europe.